On-orbit demonstration of oscillating heat pipe with check valves for space application. (5th February 2018) - Ando, Makiko; Okamoto, Atsushi; Tanaka, Kosuke; Maeda, Masakatsu; Sugita, Hiroyuki; Daimaru, Takurou; Nagai, Hiroki
Highlights: The on-orbit experiment of the OHP with check valves was conducted. The OHP operated successfully with no degradation for almost four years on orbit. Vapor-liquid behavior on orbit was clarified experimentally and numerically. Abstract: An Oscillating Heat Pipe (OHP) has high heat transport capability and enables effective heat transport even from narrow spaces, and thus is being targeted for application in the thermal management system of future spacecraft with larger heat dissipation. A Flat-plate Heat Pipe (FHP), which is an OHP with check valves sandwiched between thin aluminum alloy plates, has been developed. For applying FHPs to the thermal management system of spacecraft, the heat transfer characteristics of FHPs under microgravity conditions should first be examined. The on-orbit experiment on the FHP has been conducted since 2012 as one of the Small Demonstration Satellite-4 (SDS-4) missions. The FHP operated successfully on orbit with good heat transfer performance matching that on the ground, and with no degradation being observed for almost four years. Conversely, it was confirmed that the initial vapor-liquid distribution strongly affected the startup characteristics of FHPs, and that certain initial conditions caused startup difficulty. This paper describes the on-orbit experimental results and discusses the vapor-liquid behavior in FHPs based on those experimental results and numerical simulation.